Challenges and Outcome of Management of Gastroschisis at a Tertiary Institution in North-Eastern Nigeria - Oyinloye, Adewale O.; Abubakar, Auwal M.; Wabada, Samuel; Oyebanji, Lateef O. (Frontiers in Surgery, 2020)
Abstract Introduction Gastroschisis is a congenital anterior abdominal wall defect characterized by herniation of abdominal contents through a defect usually located to the right side of the umbilical cord. It occurs in 1 in 2000-4000 live births and is slightly commoner in males. Management has remained challenging in the low and middle-income countries, with high mortality rates. This study highlights the clinical presentation, treatment, outcomes, and challenges in the management of gastroschisis at a tertiary healthcare center in a resource-limited setting. Methods This was a retrospective review of the records of all patients with gastroschisis managed over a period of 30 months(January 2016-June 2018). Data on patients' demographics, age, birth weight, clinical presentation, method of gastroschisis reduction and closure, complications and outcomes were collated. Statistical analysis was performed using SPSS version 20. A p-value of less than 0.05 was considered significant. Results Twenty-four patients with gastroschisis were managed. Of these,18 patients had data available for analysis. There were 14 males, with a male-female ratio of 3.5:1. The median age at presentation was 11.0 hours(range 1 to 36 hours). Ten patients (55.6%) were delivered in a medical facility. One patient had type II jejunal atresia and transverse colonic atresia as associated anomalies. Improvised silos were applied by the bedside in 15(83.3%) patients, while two patients (11.1%) had primary closure under general anesthesia. One patient died before definitive treatment could be done. Sterile urobags and female condoms were used for constructing improvised silos in 9 (60%) and 6(40%) patients respectively. Eight patients who had initial silo application had complete bowel reduction over a median time of 8.0 days (mean 10.0 ± 6.5days, range 2-23days). Total parenteral nutrition was not available. The average time to commencement of feeding was 8.0 days ±6.6 ( median 6.0days, range 2 to 22 days). Full feeding was achieved in five patients(two patients in the primary closure group and three from the silo group) over a mean time of 16.8days± 10.4 ( median 14.0days). Sepsis was the commonest complication. Four patients (22.2%) survived. Conclusion Management of gastroschisis remains challenging in resource-limited regions.